A study of landscape implementation on high-rise residential in Klang Valley / Mohamad Amir Aiman Mohd Kohar ... [et al.] - Mohd Kohar, Mohamad Amir Aiman; Yusof, Ahmad Faisol; Abdul Aziz, Azhan; Jamal, Muhammad Nuhikhwan; Husain, Fazidah Hanim (2023)
A high-rise residential building is a type of housing that consists of multiple dwelling units on the same piece of property. In other word, this tall modern building also called apartment or condominium. It has been proven that proper landscape on high rise housing provides essential environmental, nice view, and recreation benefits to an open space. Applying the sustainability concept of the landscape on help to create a conducive and responsive environment of housing development. This paper presents a brief of conceptual view on the important aspects of implementation of the landscape on high-rise housing development in sub-urban areas. A study on previous research and references such as journals will be done to help providing a fact on the importance aspect of using up landscape elements in housing areas. Windows on the Park, Bandar Tun Hussein Onn, Cheras will involve in this study to be observe and analyse to interpret how the landscape give benefits to human and surrounding. It is hoped that this paper may possibly provide significant information on landscape design towards influencing the conducive environment of the high-rise housing. This study also can become a benchmark on the upgrading the sustainability of living on high-rise housing.